1978
DOI: 10.1172/jci108965
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Preservation of Ischemic Myocardium after Experimental Coronary Artery Occlusion

Abstract: A B S T R A C T The results of experiments with indirect methods have suggested that various interventions reduce infarct size after coronary artery occlusion. To determine and quantify directly both the shortand long-term effects of several interventions on myocardial salvage without relying on indirect methods, the left coronary artery was occluded in 880 rats; they were then given either no treatment or one of the following interventions: (a) hyaluronidase, an enzyme that hydrolyzes interstitial glycoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(87 citation statements)
references
References 35 publications
4
83
0
Order By: Relevance
“…Infarction was produced by left coronary arterial ligation as described previously14 and as modified by MacLean et al 15 In male Sprague-Dawley rats, the left coronary artery was ligated approximately 2 mm from its origin with a 6-0 suture. In the shamoperated rats, the suture was tied loosely so as not to obstruct coronary flow.…”
Section: Experimental Preparationsmentioning
confidence: 99%
“…Infarction was produced by left coronary arterial ligation as described previously14 and as modified by MacLean et al 15 In male Sprague-Dawley rats, the left coronary artery was ligated approximately 2 mm from its origin with a 6-0 suture. In the shamoperated rats, the suture was tied loosely so as not to obstruct coronary flow.…”
Section: Experimental Preparationsmentioning
confidence: 99%
“…This value is comparable to that reported by Weiblen et al '8 The time course of the infiltration of leukocytes into infarcted myocardium has been well characterized. In animal models of permanent coronary artery occlusion, leukocytes migrate to regions of myocardial injury within 24 hours, reaching a peak within [4][5] days. '9 However, Sommers and Jennings20 reported that reinstituting myocardial blood flow after temporary coronary artery occlusion accelerated the infiltration of inflammatory cells into injured myocardium.…”
Section: "'In Platelet Accumulation In Infarcted Myocardiummentioning
confidence: 99%
“…Several agents are effective in reducing the extent of myocardial infarction resulting from experimentally induced acute myocardial ischemia in a variety of animal models.1 One such agent, ibuprofen, is a nonsteroidal antiinflammatory compound that has been reported to exert cardioprotective effects by significantly reducing the extent of irreversible myocardial injury to experimental ischemia in the dog,2'3 the cat,4 and the rat.5 Ibuprofen renders its cardioprotective effects administered orally,3 intravenously2 or intramuscularly. 5 Several independent investigators have demonstrated protective effects in a variety of experimental models of myocardial ischemia and infarction, but little is known about ibuprofen's mechanism of action. Apparently, the beneficial effects of ibuprofen do not derive from alteration of the balance of myocardial oxygen supply and demand in a favorable manner.…”
mentioning
confidence: 99%
“…Clq and products of complement activation, e.g., C3b and CSb-9, have been detected in infarcted myocardium (11)(12)(13) and in the systemic circulation ( 14). Moreover, agents such as cobra venom factor or soluble complement receptor-i which deplete or inactivate complement have been shown to reduce infarct size in animal models (15,16). Activation of the complement system results in the liberation of several soluble products, amongst which is the cleavage product of the fifth component, CSa.…”
Section: Introductionmentioning
confidence: 99%